Mass timber wall splice connection using glued-in rods: Design methodology, implementation, and shake-table testing in a six-story building - Steven Kontra; Andre R. Barbosa; Arijit Sinha; Steve Pryor; Reid B. Zimmerman; Barbara Simpson; John W. van de Lindt; Shiling Pei; Gustavo A. Araújo R.; Morgan McBain; Ludovica Pieroni; Prashanna Mishra; et al. (Engineering Structures, 2026)

Development of a real-time hybrid simulation framework for wave energy converter mooring applications - Abilyn McConnell; Elaine Liu; Bret Bosma; Inyong Kim; Raza Ali; Barbara Simpson; Bryson Robertson (Ocean Engineering, 2026)

Hydrodynamic real-time hybrid simulation to examine the hydro-elastic response of monopile offshore wind turbines subject to nonlinear waves with higher-order effects - Akiri Seki; Jonah Gadasi; Bryson Robertson; Andreas Schellenberg; Pedro Lomonaco; Barbara Simpson (Ocean Engineering, 2026)

Pea-wheat composite bread: Effects of milling methods and NIR spectral insights - Mariana Maçãs; Barbara Biduski; Alessandro Ferragina; Antonia A.L. dos Santos; Jeremy C. Simpson; Margaritha M. Mysior; Mahesha M. Poojary; Elke K. Arendt; Eimear Gallagher (Innovative Food Science & Emerging Technologies, 2025)

Impact of Limited Degree of Freedom Drag Coefficients on a Floating Offshore Wind Turbine Simulation - Arjun Srinivas; Bryson Robertson; Jonah Benjamin Gadasi; Barbara Gwynne Simpson; Pedro Lomónaco; Jesús María Blanco Ilzarbe (Journal of Marine Science and Engineering, 2023)
The worldwide effort to design and commission floating offshore wind turbines (FOWT) is motivating the need for reliable numerical models that adequately represent their physical behavior under realistic sea states. However, properly representing the hydrodynamic quadratic damping for FOWT remains uncertain, because of its dependency on the choice of drag coefficients (dimensionless or not). It is hypothesized that the limited degree of freedom (DoF) drag coefficient formulation that uses only translational drag coefficients causes mischaracterization of the rotational DoF drag, leading to underestimation of FOWT global loads, such as tower base fore-aft shear. To address these hydrodynamic modeling uncertainties, different quadratic drag models implemented in the open-source mid-fidelity simulation tool, OpenFAST, were investigated and compared with the experimental data from the Offshore Code Comparison Collaboration, Continued, with Correlation (OC5) project. The tower base fore-aft shear and up-wave mooring line tension were compared under an irregular wave loading condition to demonstrate the effects of the different damping models. Two types of hydrodynamic quadratic drag formulations were considered: (1) member-based dimensionless drag coefficients applied only at the translational DoF (namely limited-DoF drag model) and (2) quadratic drag matrix model (in dimensional form). Based on the results, the former consistently underestimated the 95th percentile peak loads and spectral responses when compared to the OC5 experimental data. In contrast, the drag matrix models reduced errors in estimates of the tower base shear peak load by 7–10% compared to the limited-DoF drag model. The underestimation in the tower base fore-aft shear was thus inferred be related to mischaracterization of the rotational pitch drag and the heave motion/drag by the limited-DoF model.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Low levels of cannibalism increase fitness in an herbaceous tortrix moth - Jenna Simpson; Barbara Joncour; William Andrew Nelson (Behavioral Ecology and Sociobiology, 2018)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

The effect of different nutrient concentrations on the growth rate and nitrogen storage of watercress (Nasturtium officinale R. Br.) - Barbara Fernandez-Going; Thomas Even; Juliet Simpson (Hydrobiologia, 2013)

Earthworm metabolomic responses after exposure to aged PCB contaminated soils - Melissa Whitfield Åslund; Myrna J. Simpson; André J. Simpson; Barbara A. Zeeb; Allison Rutter (Ecotoxicology, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

The influence of light on the growth of watercress (Nasturtium officinale R. Br.) - Barbara Going; Juliet Simpson; Thomas Even (Hydrobiologia, 2008)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)